La plaza de ceremonias al aire libre del cementerio de Kviberg, Gotemburgo (1931-1935), Erik Gunnar Asplund | The open-air ceremonial space in Kviberg Cemetery, Gothenburg (1931–1935) Erik Gunnar Asplund - Fernández Elorza, Héctor (ZARCH, 2016)
El proyecto del Cementerio de Kviberg supuso para el arquitecto Erik Gunnar Asplund un campo de investigación donde poder experimentar con soluciones que luego aplicaría en el Cementerio del Bosque de Estocolmo. Entre los proyectos que realizó durante 1931 y 1935, la Plaza de Ceremonias al aire libre es sin duda una de las aportaciones más personales del arquitecto, y la propuesta donde más estrechamente se tratan aspectos de relación entre arquitectura y paisaje. En sus distintas versiones, inéditas hasta la fecha, Asplund utiliza la tierra, el agua y la naturaleza como medios para conseguir un espacio trascendental en relación al Hombre. The project for Kviberg Cemetery provided the architect Erik Gunnar Asplund with a field of investigation in which he could experiment with solutions that he would later apply to the Woodland Cemetery in Stockholm. Among the projects he designed between 1931 and 1935, the open-air ceremonial space is undoubtedly one of the most personal contributions made by the architect, and the design that most closely deals with aspects of the relationship between architecture and landscape. In his different versions, to date unpublished, Asplund used earth, water and nature as media to achieve a transcendental space in relation to man.